Anemia and Iron Deficiency Diagnosis, Management and Treatment in Chronic Kidney Disease - Consensus and Agreement through a Delphi Panel - Ferreira, A (2021)
Background: Anemia is a common complication of Chronic Kidney Disease (CKD), in which iron deficiency’s (ID) role is frequently underrated. In CKD, anemia has been associated with higher morbidity and lower quality of life. Nonetheless, reported treatment rates of anemia in CKD are low and guidelines’ variability and/or absence for its management and treatment may be preventing patients from receiving optimal treatment. Within this context, we aimed to assess the agreement level on anemia and iron deficiency diagnosis, management, and treatment in CKD patients, by Portuguese physicians in Nephrology, through a Delphi Panel. Methods: A group of seven medical experts in Nephrology and Transfusion Medicine was assembled, and a focus group was conducted, in which 28 statements were agreed upon. Then, a two-round Delphi Panel using a Likert scale was conducted online, inviting Portuguese Society of Nephrology associates to participate. Results: Answers were collected from 76 participants in Round 1 and consensus level was obtained for 1 statement, 57 (75%) respondents fully disagreeing on transfusing all patients with hemoglobin below 9 g/dl, regardless of the clinical situation. The remaining 27 statements were used in Round 2, none obtaining consensus level and 14 statements being categorized as qualified majority: 4 on diagnosis, 3 on disease management, and 7 on treatment. Discussion: Our study showed a lack of consensus on diagnosis, management, and treatment of anemia in CKD patients among the nephrology community in Portugal. Overall, our results illustrated the heterogeneity of national clinical practices in: laboratory parameters’ choice; cutoff values defining anemia and/or ID; parameter-based therapeutic decisions. Nonetheless, it was shown clear that patient’s individual characteristics, clinical settings, and the physician’s “clinical sense” seem to be considered to a further extent than the available guidelines. Future studies should be considered to develop recommendations that can be widely accepted.